Wear-Resistant Fe6AlCoCrNi Medium-Entropy Alloy Coating Made by Laser Cladding - Ke Chen; Hongbo Pan; Mingyu Wu; Xianfa Wang; Dongyang Li (Metals, 2022)
An Fe6AlCoCrNi medium-entropy (MEA) coating was coated on a steel substrate by laser cladding. The micro-structure, crystal structure, phases, and wear properties of the coating were investigated. The coating was mainly composed of a dendritic face-center cubic (FCC) phase, which showed preferred crystal orientation of <2 0 0>, normal to the coating surface, and a body-center cubic (BCC) phase. The MEA coating exhibited satisfactory rigidity with superior wear resistance at different loads and temperatures, much higher than that of the steel substrate. When the test temperature increased from 293 K to 573 K, the coefficient of friction (COF) of the coating markedly decreased from about 0.75 to 0.35; a large decrease in wear was also observed. The wear mechanism of the MEA coating was abrasion wear at room temperature, while the wear of the coating at high temperatures involved considerable oxidation, which enhanced the wear resistance of the coating.